Beyond the Standard Model Higgs sectors - Malinauskas, A (2019)
Although the experimentally detected 125 GeV spin-0 resonance has properties very close to the one predicted by the Standard Model, it is still possible that the Higgs sector in nature is not SM-like. In this work we will discuss two projects investigating the experimental validity of THDM (Two Higgs Doublet Model) and THDM+S models.